Is it worth being good? The efficiency and risk of socially responsible investing in light of various empirical studies - Tomasz Jedynak (e-Finanse: Financial Internet Quarterly, 2017)
The paper discusses the issue of the effects of using SRI strategies on performance and risk of investment portfolios. During the research procedure, a number of goals were executed which is reflected by the article's structure. In the first place, potential directions of the effects of using SRI strategies on portfolio parameters were indicated. Generally, these are hypotheses about 1) positive; 2) negative; 3) neutral impacts of SRI on investment portfolio parameters. Then the main streams in the research on SRI were identified. These streams are mainly based on: modern portfolio theory, the costs of an asset selection conception and the analysis of the correlation between CSR policy and company profitability. Moreover, the research stream which focuses on the relationship between the social responsibility of business and its competitive position was identified. The performed wide review of the literature raising the issues of performance and risk of SRI allows us to make an attempt to synthesize the results obtained by various authors. This synthesis is based on criteria such as: subjective scope, geographical span, methodology and findings of particular research. The main finding of the research is that despite many attempts in which various methods were used, so far there is no firm evidence to support or reject any of the above formulated hypotheses.
Keywords: G11; M14; Q1; 330; SRI; socially responsible investment; portfolio performance; ethical investment